On stability of motion of a symmetric body placed on a vibrating base - Koshlyakov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider the problem of stabilization of a symmetric solid body rotating about a fixed point and show that its unstable states can be stabilized by vertical vibration.